2004
DOI: 10.1002/jsfa.1656
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in muscle fibre area, gaping, texture, colour and collagen in triploid and diploid Atlantic salmon (Salmo salar L)

Abstract: Diploid and triploid Atlantic salmon were reared for 32 months in seawater, from October 1998 to January 2000. During this period of time, four samplings were taken to study differences in quality traits and chemical components in the flesh between diploid and triploid Atlantic salmon. Season was found to be the dominant factor explaining the variation in flesh quality traits in both triploid and diploid fish. Ploidy affected the majority of investigated variables while body size had lesser impact. Triploid At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 56 publications
7
36
1
Order By: Relevance
“…In the present study, we observed that triploid fish had larger white muscle fibers than diploid fish (+9% and + 15% of the mean diameter for the L line and F line, respectively). Such an effect of triploidy on muscle fibers size was already reported in salmonids (Bjørnevik et al, 2004;Johnston et al, 1999;Poontawee et al, 2007;Sigurgisladottir et al, 2001;Suresh and Sheehan, 1998). In the present study, higher values of lightness were found for both raw and cooked fillets of triploid fish.…”
Section: Effects Of Triploidy On Flesh Qualitysupporting
confidence: 75%
See 1 more Smart Citation
“…In the present study, we observed that triploid fish had larger white muscle fibers than diploid fish (+9% and + 15% of the mean diameter for the L line and F line, respectively). Such an effect of triploidy on muscle fibers size was already reported in salmonids (Bjørnevik et al, 2004;Johnston et al, 1999;Poontawee et al, 2007;Sigurgisladottir et al, 2001;Suresh and Sheehan, 1998). In the present study, higher values of lightness were found for both raw and cooked fillets of triploid fish.…”
Section: Effects Of Triploidy On Flesh Qualitysupporting
confidence: 75%
“…These effects of triploidy on fish biology may lead to consequences in flesh quality, as reported in various salmonid species. Differences between diploid and triploid fish were demonstrated in muscle fiber size, fillet gaping, color, texture and some muscle biochemical characteristics, such as protein solubility (Bjørnevik et al, 2004;Gomez-Guillén et al, 2000;Poontawee et al, 2007;Werner et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Instruments to measure texture do not have the human ability to evaluate and to interpret multivariate input [39]. If texture can be specified in an early processing step, inferior quality in the final product can be reduced [36,38,40,41]. …”
Section: Firmness: a Quality For Good Fish Texturementioning
confidence: 99%
“…Texture and colour differences were attributed to variation in muscle cell size. Moreover, the relationship among fillet texture, fibre arrangement, and density is not consistent [17,34,40].…”
Section: Muscle Cell Biologymentioning
confidence: 99%
“…There has been little investigation of the effects of ploidy on the quality characteristics of (lower L*-value) and more reddish (higher a*-value) compared to that of diploids (Bjørnevik,87 Espe, Beattie, Nortvedt, & Kiessling, 2004 …”
mentioning
confidence: 99%